Production, characterization, microbial inhibition, and in vivo toxicity of cold atmospheric plasma activated water. (March 2023) - Katsaros, George; Giannoglou, Marianna; Chanioti, Sofia; Roufou, Styliani; Javaheri, Aftab; de Oliveira Mallia, Jefferson; Gatt, Ruben; Agalou, Adamantia; Beis, Dimitris; Valdramidis, Vasilis
Abstract: Cold atmospheric plasma activated water (PAW) was produced at various Reactive Nitrogen Oxygen Species (RONS) concentrations. PAW was characterized and in vivo toxicological studies were conducted, using the zebrafish embryo acute toxicity test (OECD 236). Danio rerio (zebrafish), were raised in standard egg PAW of various RONS concentrations and their lethality was monitored. The thresholds for no lethality and simultaneously no obvious morphological phenotypes were determined as approximately 30 mg/L H2 O2 concentration, while for NO3 − concentration, the values were also correlated to the pH of the solution used. The pH-value of 3.85 was also a measurable threshold for the lethality of the embryos. Toxic and non-toxic PAW were used as medium to assess their inhibitory potential for Escherichia coli and Enterococcus faecium . The results indicated that PAW delayed the recovery time or even resulted in no growth of these microorganisms compared to control samples. Highlights: Zebrafish were raised in various concentrations of reactive oxygen species of PAW. Threshold for zebrafish lethality was determined as 30 mg/L H2 O2 concentration. Threshold for NO3 − was 7–15 mg/L, depending on pH value of the solution. A pH-value equal to 3.85 was defined as threshold for zebrafish lethality. Non-toxic PAW efficiently delayed growth of pathogens or even totally inactivated.